The Influence of Liquidity, Profitability, and Solavability on Share Prices in Registered Banking Companies On the Indonesian Stock Exchange - Tiara (Journal GoodWill, 2022)
This research delves into the relationship between Liquidity, Profitability, Solvency, and Stock Prices. Conducted through descriptive quantitative methods, the study examines financial statements from banking companies listed on the Indonesia Stock Exchange from 2018 to 2020. The findings reveal compelling insights: liquidity exhibits a positive and statistically significant impact on stock prices, indicating that investors favor stocks of companies with higher liquidity. Similarly, profitability emerges as a key driver, with a positive and significant influence on stock prices. This suggests that investors are attracted to banks with strong profitability prospects. Interestingly, solvency demonstrates a negative and significant effect on stock prices. This implies that while solvency is essential for financial stability, investors may prioritize other factors such as liquidity and profitability when assessing stock value. Moreover, when considered together, liquidity, profitability, and solvency collectively influence stock prices, emphasizing the multifaceted nature of stock valuation. These findings offer valuable insights for investors navigating the banking sector. By understanding the nuanced interplay between liquidity, profitability, solvency, and stock prices, investors can make more informed decisions. For instance, investors may prioritize banks with robust liquidity and profitability metrics while being mindful of solvency considerations. Overall, this study provides practical implications for investors seeking to optimize their investment strategies within the banking industry.